2021
DOI: 10.3389/fnhum.2021.645209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Dorsolateral Prefrontal Cortex for Speech and Language Processing

Abstract: This review article summarizes various functions of the dorsolateral prefrontal cortex (DLPFC) that are related to language processing. To this end, its connectivity with the left-dominant perisylvian language network was considered, as well as its interaction with other functional networks that, directly or indirectly, contribute to language processing. Language-related functions of the DLPFC comprise various aspects of pragmatic processing such as discourse management, integration of prosody, interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 186 publications
(201 reference statements)
2
77
0
5
Order By: Relevance
“…According to Table 2 as well as Section 3.4 , the supporting role of brain regions is maximal within the frontoparietal, dorsal attention, visual, and default mode networks such as DLPFC and PGi , regardless of the resting state or task engagement. This finding is in line with the previous studies showing the dominant role of these brain areas in internal processing and the facilitation of information exchange in functional brain networks [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to Table 2 as well as Section 3.4 , the supporting role of brain regions is maximal within the frontoparietal, dorsal attention, visual, and default mode networks such as DLPFC and PGi , regardless of the resting state or task engagement. This finding is in line with the previous studies showing the dominant role of these brain areas in internal processing and the facilitation of information exchange in functional brain networks [ 73 , 74 ].…”
Section: Discussionsupporting
confidence: 93%
“…For neural plastic changes, we found that AC training increased the rGMV in the R. DLPFC, L. ITG, OFC, and right cerebellum (lobule 7 Crus 1). The DLPFC is suggested to be involved in central executive processes ( Hertrich et al, 2021 ). Particularly relevant to multiple tasks, the DLPFC is involved in scheduling processes in complex tasks (task management) ( Smith and Jonides, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Speech processing models propose that temporal information and memory representations are first integrated in the dorsolateral prefrontal cortex (DLPFC) to facilitate perception (Kotz & Schwartze, 2010, 2016. Given the functional role of the DLPFC in language processing has been mostly attributed to higher-level processing such as pragmatics, sentence processing, or comprehension of non-literal language (for review, see Hertrich et al, 2021), this is consistent with the lack of clear interactive effects at the sublexical level.…”
Section: Dissociable Processes Underlying Formal and Temporal Predict...mentioning
confidence: 54%